Analysis of KFC's Strategy in Dealing with Pork Content Issues (Qualitative Descriptive Study on the Operational Teams at KFC Outlets in Surabaya-Sidoarjo) - Yahezkiel Ivandro; Fransiska Nikola; Alfian Affandi; Carissa Emilyana; Monica Karenina; Dyva Claretta; Dian Hutami Rahmawati (2022)
A company can use issue management theory as a solution to overcome problems in the form of negative issues. Last August, KFC was hit by the issue of pork in its food content. This study discusses how KFC designs strategies to address these issues. This strategy also includes how issue management is implemented by KFC. This research uses qualitative methods with data collection techniques of interviews and supported by literature review. To determine the research informants, the researchers chose the Operational Teams at KFC Outlets in Surabaya-Sidoarjo with the consideration they understood the issue from both sides, both from the KFC side and from the consumers. The result of this study is that KFC rejects all issues that say its food contains pork. KFC has also carried out the issue management stage by clarifying the rumors and strengthened by a statement from the MUI and a halal certificate.